Ellsworth Kelly : Red Green Blue : Paintings and Studies, 1958-1965 - Davies, Hugh M; Bernstein, Roberta; Matsumoto, Takaaki; Hickey, Dave; Kamps, Toby; Rich, Sarah K.; Museum of Contemporary Art San Diego, San Diego; The Museum of Fine Arts, Houston; Whitney Museum of American Art, New York (San Diego : Museum of Contemporary Art San Diego, 2002)
Ellsworth Kelly : Red green blue - Paintings and studies, 1958-1965 is the first exhibition catalogue to focus on a grand, powerful body of paintings and related studies by American artist Ellsworth Kelly. Through these works, Kelly demostrated his vibrant originality and defined the interests that still drive his work today. Bringing together twenty-one major "figure / ground" paintings - rectangular canvases in which forms in one or two colors are balanced against third "ground" color - and thirty-four drawings, collages, and photographs, Red green blue illuminates the processes by which Kelly distills his lines, forms, and colors from real-world sources. The project focuses on a selection of large-scale paintings widely ackowledged as masterpieces that employ precisely balanced shapes and the intrinsic clashes and harmonies of the colors red, green, and blue to create bold and dynamic compositional balances. Essays by exhibition curator Toby Kamps, critic Dave Hickey, and scholars Roberta Bernstein and Sarah K. Rich illuminate the ramifications of this breakthrough period in Kelly's career. Red green blue accompanies an exhibition organized by the museum of Contemporary aRt san Diego and traveling to the Museum of Fine Arts, Houston, and the whitney Museum of American Art, New York.
Ellsworth Kelly : Red Green Blue, Museum of Contemporary Art, San Diego, January 19 - April 14, 2003 / The Museum of Fine Arts, Houston, April 27 - July 27, 2003 / Whitney Museum of American Art, New York, August 10 - November 3, 2003
bibliog. p. 126-127
biog. p. 121-125
Engels
boek
Keywords: Kelly, Ellsworth